PHYTOSOCIOLOGICAL RESEARCH OF THE PURE BETULA PENDULA FORESTS IN GREECE: RHODOPE MOUNTAIN RANGE (NE GREECE) - K. THEODOROPOULOS (Annali di Botanica, 2003)
The geographical distribution of the birch (BeTula pendula Roth.) in Greece is Limited to the northern mountains (Varnous, Voras, Vennio, Paiko, Beles, Orvilos, Lailias, Pangeo, Phalakro and Rhooope). The unique extensive pure Betula penduta - forest, which covers an area of about 1755 ha, occurs in the western part of the Rhodope mountain range. The other appearances of birch in the Greek area are limited either to small stands or to individuals in mixture with other forest trees. The Betula pendula forest in western Rhodope have been studied using the Braun - B1anquet mtethod with 36 phytosociological relevés. Two associations. Querco dalechampii - Betuletum pendulae (Quercetalia pubescentis) and Fago sylvalicae - Betuletum pendulae (Fagetali sylvAticae ), as well as rurther subdivisions, are distinguished. Their syntaxonomy as well as informatìon about the site characteristics, structure and syndynamical position of the distinguished communities are given.